Impact of genetic polymorphism of metabolic pathway of methotrexate and survival rate of mexican children will all - Zaruma-Torres, Fausto Leonardo; Lares-Asseff, Ismael; Reyes-Espinoza, Aarón; Loera-Castañeda, Verónica; Almanza-Reyes, Horacio; Arias Pelaez, Maria Cristina (Vitae, 2016)
Background: Acute lymphoblastic leukemia (ALL) is a major cancer disease in Mexican pediatric population, were the genotype could affect the effectiveness of chemotherapy in which the methotrexate (MTX) is involved and consequently the time of disease free survival and overall survival. Objective: Determine the association of 10 genetic polymorphisms of the folate pathway: in cellular carriers (COL18A1, SLC19A1, ABCB1 and ABCC5) and in enzymes such as folylpolyglutamate synthetase (FPGS) and xanthine oxidase (XO), with survival of children with acute lymphoblastic leukemia. Methods: Thirtynine children with acute lymphoblastic leukemia from the State Cancer Center in Durango (Mexico) treated with MTX and 102 healthy controls, were qPCR analyzed for 10 polymorphisms in the folate pathway. During 5 years of follow up, the disease-free survival and overall survival rates were investigated in relation with their genotypes. Results: Four polymorphisms were not found in Hardy-Weinberg Equilibrium COL18A1 (rs2274808), ABCC5 (rs9838667 and rs3792585) and XO (rs170113685). Only XO (rs170113685) was associated with risk of being present in patients with ALL whose odds ratio was 9.771 (95% 4.974-19.196, p=0.001). The polymorphism rs1544105 for FPGS affected disease free survival and overall survival (Log Rank test p<0.05). Conclusion: Polymorphism (rs17011368) of XO showed risk association for acute lymphoblastic leukemia; likewise, an important association was found between carriers of the FPGS (rs1544105) and increased survival times of patients treated with methotrexate.Keywords: Methotrexate, XO, FPGS, survival, Precursor Cell Lymphoblastic Leukemia-